The role of accounting disclosure in raising the quality of tax settling accounts: Applied research in the General Commission for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to highlight the role of accounting disclosure in raising the quality of tax settling accounts so as to enhance confidence between taxpayers (corporates) and tax authority, standing over companies commitment to take care of  their financial statements which are  prepared to the appropriate accounting disclosure of tax authority. It has been noticed that a good disclosure about the results of the activity leads to the acceptance of the tax authority to the results which are stated by the financial statements and the tax is linked on its bases.   The researcher depends on the deductive approach which based on Arabic and foreign references, books, researches, previous  studies,  scientific  symposium as well as the scientific aspect which richens  the study in order to derive the rules and basis for accounting  disclosure in the financial reports. The sample and community of the study were the registered corporates at the corporates departments at the General Commission of Tax.Some of them presented inaccurate information, while others presented appropriate information about their activities which the financial authority dealt with in good way, by accepting the results at their accountings. Many of the financial statements of hose corporate have been chosen for 2012-2010 and have been analyzed. The findings of the study indicate that:      • Tax authority represents one of the beneficiaries of the financial reports that tax authority depends on in the tax settling the books as the basis for calculating the taxable income process. this requires to highlight the role of accounting disclosure of financial reports submitted to the tax authority by companies.• The estimation at the income submitted to tax is the most important  task of tax settling accounts because the administration is required to pay attention to two opposite interests, the interest of the taxpayers and the interest of the general treasury therefore, the subject of the quality of tax settling accounts takes a great position from the aspect of tax revenue and the fair of distribution for  this, many countries interest in this subject.• The good disclosure creates good history to the corporate and comptroller of the financial authority. This leads to the acceptance of that authority to the results at the financial statements and the tax is linked on its bases. This represents the aim of the taxpayer in accepting its accounting results and achieving the message at the comptroller regarding the quality of its work in promoting accounting disclosure. Key recommendations are as follows:• Highlighting the role of accounting disclosure of financial reports, which are submitted to the tax authority by the companies, as that authority, Is one of the main beneficiaries of these reports, which the authority relies on in the tax process of settling accounts.• The importance of making of forts by the tax administration to improve the level of estimating the income submitted to tax. This is the accurate and most complex task of tax setting account, and taking into consideration the interest of the taxpayer and the interest of general treasury.The importance of taking care of the disclosure its quality and its authenticity by the taxpayer, accountants and comptroller. It creates a good history which the financial authority and other users relied on additionally the financial authority has great role to creates the loyalty spirit for this profession by the accountants and comptroller.